PENGABDIAN KEPADA MASYARAKAT UNHAN RI MENGENAI PENINGKATAN TOLERANSI DAN CINTA DAMAI MELALUI PENDIDIKAN BELA NEGARA PADA SMA KARAKTER DEPOK - Achmed Sukendro; Relycia Solihin; Adelya Mayangsari (Bajang Institute, 2024)
Technological advancements often lead to negative impacts such as diminishing empathy and intolerance towards the environment, and even contribute to the rise of radicalism in public spaces in Indonesia. This phenomenon is evident among students, despite schools being intended as safe learning environments. Addressing these issues requires preventive measures, including raising awareness of the dangers of radicalism through national defense education at SMA Karakter Depok. One effective method involves direct outreach, such as seminars for students in grades X and XI held in the school's multipurpose hall. This community engagement has proceeded smoothly and constructively, successfully fostering attitudes of tolerance, peace advocacy, and a heightened sense of national pride and civic duty. Consequently, it is hoped that a strong, patriotic younger generation will emerge, ready to sacrifice for the security of the nation against various threats